Evaluating the relevance of surgical margins. Part one: The problems with current methodology. (25th November 2022) - Bray, Jonathan; Eward, Will; Breen, Matthew
Abstract: The goal of cancer surgery is to achieve a "clean" microscopic resection, with no residual tumour remaining in the wound. To achieve that goal, the surgeon typically incorporates a measured buffer of grossly normal tissue about the entire circumference of the tumour. Microscopic analysis of the resection boundaries is then performed to determine if all traces of the tumour have been completely removed. This analysis is thought to provide a surrogate indication as to the likelihood for that tumour to recur after surgery. However, it is recognised that tumour recurrence may not occur even when microscopic evidence of tumour has been identified at the resection margins, and recurrence can also occur when conventional histology has considered the tumour to have been completely removed. The explanations for this dichotomy are numerous and include technical and practical limitations of the processing methodology, and also several surgeon‐related and tumour‐related reasons. Ultimately, the inability to confidently determine when a tumour has been removed sufficiently to prevent recurrence can impact on the ability to provide owners with confident treatment advice. In this article, the authors describe the challenges with defining the true extent of the tumour margin from the perspective of the surgeon, the pathologist and the tumour. The authors also provide an analysis of why our current efforts to ensure that all traces of the local tumour have been successfully removed may provide an imperfect assessment of the risk of recurrence.